2021
DOI: 10.1002/arch.21849
|View full text |Cite
|
Sign up to set email alerts
|

Roles of matrix metalloproteinases in development, immunology, and ovulation in fruit Fly (Drosophila)

Abstract: Matrix metalloproteinase (MMP), a protease enzyme, participates in proteolytic cleavage of extracellular matrix proteins from Drosophila and mammals. But, recent studies have revealed other physiologically important roles of MMP in Drosophila. MMP contributes to cardioblast movement and distribution of collagen proteins during cardiogenesis in developing Drosophila. Tissue remodeling, especially tracheal development is also maintained by MMP. MMP regulates certain immunological functions in Drosophila such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The importance of MMPs in protein degradation can be evidenced by their wide distribution in different groups of vertebrates [44], including mammals [6][7][8][9], birds [45], reptiles [46,47], amphibians [48] and fish [10], as well as insects [49] and echinoderms [50].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of MMPs in protein degradation can be evidenced by their wide distribution in different groups of vertebrates [44], including mammals [6][7][8][9], birds [45], reptiles [46,47], amphibians [48] and fish [10], as well as insects [49] and echinoderms [50].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in the last few decades it has been reported that metastatic behavior of Drosophila tumors depends on Matrix metalloproteinases (MMPs) to support the microenvironment of cancer cells [5]. Matrix metalloproteinases (MMPs), one of the metastasis biomarker, are extracellular calcium-dependent zinc-containing proteases, which regulate many signaling pathways involved in cell differentiation, proliferation, and metastasis [6]. In humans there are 24 MMPs, of which, 7 MMPs are GPI (Glycosylphoshatidylinositol) anchored and 17 MMPs are soluble secreted proteinases [7].…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are classified into 3 groups: MMP1, MMP2, and MMP3 in insects (Altincicek & Vilcinskas, 2008;Knorr et al, 2009;Kantor et al, 2017;Liu et al, 2022). In Drosophila, MMP1 is involved in trachea development and nerve development of embryos, fat body dissociation, while MMP2 mutations result in defective histolysis, but both MMP1 and MMP2 are required for tissue remodeling and wound healing (Bindhani et al, 2022). Furthermore, prior studies demonstrated that c-Jun N-terminal kinase stimulates MMP1 production, which is vital for metastasis in hindgut cells (Uhlirova & Bohmann, 2006;Weston & Davis, 2007;Bindhani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prior studies demonstrated that c‐Jun N‐terminal kinase stimulates MMP1 production, which is vital for metastasis in hindgut cells (Uhlirova & Bohmann, 2006; Weston & Davis, 2007; Bindhani et al. , 2022). In agreement with the findings in Drosophila , functional assays showed that the functions of MMPs are conserved in Bombyx mori , in which 3 MMP members have demonstrated their pleiotropic effects in immunity and metamorphosis (Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation